15-Lipoxygenase/15-hydroxyeicosanoid and activator protein 1 contribute to hypoxia-induced pulmonary artery smooth muscle cells phenotype alteration. (August 2018) - Xing, Yan; Zheng, Xiaodong; Qi, Jing; Fu, Yao; Cao, Weiwei; Li, Jiali; Zhu, Daling
Highlights: Hypoxia increased AP-1 expression through 15-lipoxygenase/15-hydroxyeicosanoid signaling pathway in PASMCs. AP-1 was involved in hypoxia/15-lipoxygenase/15-hydroxyeicosanoid induced PASMCs proliferation and cell cycle progression. AP-1 regulated the expression of 15-LOX through a feedback mechanism. Abstract: We have previously shown that 15-lipoxygenase (15-LOX) and its metabolite 15-hydroxyeicosanoid (15-HETE) play a critical role on hypoxia-triggered pulmonary artery smooth muscle cell (PASMC) phenotype alteration through multifactorial pathways, like extracellular signal-regulated kinase and p38 mitogen-activated protein kinases. Here, we hypothesize that activator protein 1 (AP-1) was also involved in the PASMC phenotype alteration. Hypoxia elevated AP-1 expression in pulmonary arterials and in cultured PASMCs with a time-dependent manner. Both the gene disruption and pharmacological inactivation of 15-lipoxygenase (15-LOX) significantly attenuated the hypoxia-elevated AP-1 expression. Silencing of AP-1 with small interference RNA abrogated the hypoxia- and 15-HETE-increased cell viability, proliferating cell nuclear antigen expression, and Ki67 and α-tubulin staining. Moreover, AP-1 knockdown prevented hypoxia- and 15-HETE-promoted cyclin D1 expression and subsequent cell cycle progression into G2/M+S phase. Interestingly, AP-1 knockdown also inhibited the expression of 15-LOX, indicating a feedback regulation of 15-LOX/15-HETE signaling by AP-1. These findings shed light on the involvement of AP-1 in the PASMCs phenotype alteration via the hypoxia/15-LOX/15-HETE signaling.